HUBUNGAN MOTIVASI DAN SIKAP DENGAN KEMAMPUAN MEMBACA BAHASA INGGRIS PADA SISWA DI MADRASAH ALIYAH AL-ISTIQOMAH KABUPATEN TANGERANG TAHUN 2020 - Purwani, Retno; Cipto, Dear Ayu Dana; Ratnasari, Febi (Nusantara Hasana Journal, 2022)
English is very much needed in its field or work, both at home and abroad, because there are so many sources of information that we get from abroad. This type of research is descriptive without using a cross-sectional approach. With a total sample size of 126 respondents in grades 1 and 2 at Madrasah Aliyah Al-Istiqomah Tangerang Regency. The statistical test used is the Chi Square Test. Based on the chi-square test with 126 respondents, it was found that the p-value = 0.000 <0.05, it can be stated that Ho is rejected, meaning that there is a relationship between motivation and attitude with the ability to read English at Madrasah Aliyah Al-Istiqomah Tangerang 2020. The results of this study are that there is a relationship between motivation and the ability to read English and there is a relationship between attitudes and the ability to read English. Suggestions for further research are to look for relationships due to the effects of each of the variables studied, as well as to look for variables that affect between motivation and attitudes between reading skills in English.